Metode Tegar Pada Guru PAUD di Kota Semarang (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this service is to make the product development of basic movement skills as walking, running and jumping to early childhood. The purpose of this service is to socialize TEGAR model of the development of methods to improve basic motor skills to walk, run and jump on early childhood education in the city of Semarang. The data collected in this study is qualitative data. The main instrument used in this devotion is the response of the correspondent. Data were collected from observation, interviews, and documentation. The main procedures in this devotion is held socialization TEGAR method for early childhood teachers to be used as a reference for improving the basic motion at an early age. The result can be concluded that: (1) a method TEGAR capable and suitable for early childhood; (2) TEGAR method is able to improve motoric base for early childhood; (3) the support and enthusiasm of early childhood teachers to implement the method TEGAR.